Functional Genomics in the Mouse: Phenotype-Based Mutagenesis Screens - Schimenti, John; Bucan, Maja

(untitled) (Genome Research, 1998)
Significant progress has been made in sequencing the genomes of several model organisms, and efforts are now underway to complete the sequencing of the human genome. In parallel with this effort, new approaches are being developed for the elucidation of the functional content of the human genome. The mouse will have an important role in this phase of the genome project as a model system. In this review we discuss and compare classical genetic approaches to gene function—phenotype-based mutagenesis screens aimed at the establishment of a large collection of single gene mutations affecting a wide range of phenotypic traits in the mouse. Whereas large scale genome-wide screens that are directed at the identification of all loci contributing to a specific phenotype may be impractical, region-specific saturation screens that provide mutations within a delimited chromosomal region are a feasible alternative. Region-specific screens in the mouse can be performed in only two generations by combining high-efficiency chemical mutagenesis with deletion complexes generated using embryonic stem (ES) cells. The ability to create and analyze deletion complexes rapidly, as well as to map novel chemically-induced mutations within these complexes, will facilitate systematic functional analysis of the mouse genome and corresponding gene sequences in humans. Furthermore, as the extent of the mouse genome sequencing effort is still uncertain, we underscore a necessity to direct sequencing efforts to those chromosomal regions that are targets for extensive mutagenesis screens.